2009
DOI: 10.3171/2009.6.spine091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spinal cord signal intensity changes on clinical outcome after surgery for cervical spondylotic myelopathy

Abstract: Object The presence of intramedullary T2 high signal intensity changes in patients with cervical spondylotic myelopathy (CSM) indicates the existence of a chronic spinal cord compressive lesion. However, the prognostic significance of signal intensity changes remains controversial. The purpose of this study was to evaluate the effect of spinal cord T2 signal intensity changes on the outcome after surgery for CSM. Method Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 33 publications
2
57
0
1
Order By: Relevance
“…Many authors demonstrated that the surgical outcomes of cervical myelopathy have been reported variously depending on affected level number, treatment modality, and surgical options including anterior cervical fusion, posterior fusion, or cervical laminoplasty [5,20]. There has been no study to compare the clinical outcome of none SI change and intramedullary increased SI change to that of contrast (Gd-DTPA) enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors demonstrated that the surgical outcomes of cervical myelopathy have been reported variously depending on affected level number, treatment modality, and surgical options including anterior cervical fusion, posterior fusion, or cervical laminoplasty [5,20]. There has been no study to compare the clinical outcome of none SI change and intramedullary increased SI change to that of contrast (Gd-DTPA) enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…6,16,25,30,36,37 The physiological mechanisms underlying the recovery of motor function after CSM surgery are poorly understood.…”
mentioning
confidence: 99%
“…Chatley et al 12 found that in their series of 67 patients with CSM the mean age was 47.1years with a range of 22 to 65 years. In this study, the mean age was 53.11 years with SD of ±10.71 years.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents have multiple responses, like if one patient had weakness in upper limbs, the patient may also have had neck pain or numbness & tingling sensation. Chatley et al 12 shows the presenting complaints in their study as gait dysfunction (86.0%), limb weakness (78.1%), numbness & tingling (51.6%) and neck pain (39.1%). In this present study, there were 5 motor myelopathic signs being present in the respondents named hyperreflexia, Hoffmann's sign, IBR (Inverted brachioradialis reflex), ankle clonus and Babinski sign.…”
Section: Discussionmentioning
confidence: 99%